The nature of grain boundaries in alumina fabricated by fast sintering - Zhang, J; Meng, F; Todd, R; Fu, Z (Elsevier, 2010)
Fast sintering processes offer promising new routes for the fabrication of bulk ceramics but it is not clear that the microstructural details and properties resulting from a very short, rapid densification procedure are the same in all respects as those resulting from traditional sintering. Here, not fully relaxed grains and their weak mechanical properties of as-prepared nanoscale alumina are described. It was found that low temperature annealing did not cause grain growth but allowed normal boundaries to develop.